2013
DOI: 10.3855/jidc.2769
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory predictors of outcome in cerebral malaria in suburban Nigeria

Abstract: CM is associated with high mortality and serious sequelae. Affected children should be given proactive management and monitored closely to reduce the frequency of adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
3
14
1
Order By: Relevance
“…This result is comparable to reports in a previous study, other African counties, and India showing mortality less than 5% [3,14,18,23]. In contrast, other studies from Uganda and Nigeria reported higher mortality rates (14% and 13.6% respectively) [12,25]. This variation could be related to many factors including late presentation, co-morbidities and quality of local health care.…”
Section: Treatmentsupporting
confidence: 84%
See 1 more Smart Citation
“…This result is comparable to reports in a previous study, other African counties, and India showing mortality less than 5% [3,14,18,23]. In contrast, other studies from Uganda and Nigeria reported higher mortality rates (14% and 13.6% respectively) [12,25]. This variation could be related to many factors including late presentation, co-morbidities and quality of local health care.…”
Section: Treatmentsupporting
confidence: 84%
“…In this study, P. falciparum infection and low-density parasitemia were not statistically significantly associated with CM as has been reported in Cameroon, India, and Nigeria [11,14,25]. We recorded AKI in 7.4% of our children with severe disease.…”
Section: Treatmentsupporting
confidence: 65%
“…The same was observed in NoECMs. High levels of creatinine, observed principally in ECM and NoECM HP rats, have also been reported in children suffering of CM in Africa where hypercreatinemia was reported to be a risk factor of mortality [37,51]. This increase could be linked to renal failure also described in severe malaria [2,52].…”
Section: Resultsmentioning
confidence: 85%
“…While the mortality attributed to malaria in India7 is 0.05%, the figure multiplies manifold in those with cerebral involvement. Mortality in cerebral malaria was reported as 5.5–7% in children in Africa3,8 and 20% in adults in South Asia 9. Concomitant acute renal failure and metabolic acidosis cause a 6-fold increase in mortality suggesting associated vital organ dysfunction has a summative effect on mortality in severe malaria 10.…”
Section: Introductionmentioning
confidence: 99%